Navigating Career Decisions: The Influence of Gender Perception among High School Students - Hadi, Abdul; Aryani, Eka (Guidance and Counseling Study Program, Pattimura University, 2023)
This study delves deeply into the intricate association between perceived gender roles and career selection among students in the twelfth grade at MAN 2 Bantul. It utilizes a sophisticated correlational research design to draw precise and nuanced conclusions about the intricate dynamics between these two constructs. The analytic method employed was a product-moment correlation, which robustly demonstrated the existence of a significant and strong positive relationship between gender perceptions and career choices. The study also unearthed an intricate web of influential factors, with social support from family, teachers, and peers being pivotal in shaping students' career decision-making trajectories. Additionally, our findings provide substantial evidence suggesting a negative correlation between perceived parental and teacher support and the complexity of career decision-making. Conversely, we observed a positive correlation between the frequency of classmate and close friend social support and career decision-making difficulties. This research enhances our understanding of gender as a socially constructed concept deeply entwined with cultural roles, shaping the trajectory of career choices. It also underscores the profound influence of societal norms and perceptions regarding gender roles on students' career preferences. This influence signifies the necessity of further research into the subtle ways these perceptions may shape or restrict career aspirations. It is evident that guidance and counseling services have a pivotal role in helping students navigate the often complex and challenging landscape of career decisions. They are also instrumental in providing students with the necessary understanding to identify and challenge prevailing gender perceptions that may inadvertently impact their career decisions. Therefore, the results obtained from this research highlight the pressing need for an educational environment that is both cognizant and inclusive of the various gender perceptions in existence and their potential impacts on career decisions. This is crucial in ensuring informed guidance, fostering student self-efficacy, and empowering students in their journey of selecting and navigating their respective career paths effectively.